KAWIN BEDA AGAMA DALAM LEGISLASI HUKUM PERKAWINAN INDONESIA PERSPEKTIF HAM - Tobroni, Faiq (Islamic University of Indonesia, 2010)
In the universal standards and appropriate covenants on civil and political rights is stated that any institution is not allowed to handcuff someones freedom to choose a partner. However, in practice in the context of Indonesia is not as easy as that discourse. In this context the concept of utilitarianism Maqashid Shariah and legal formulation laid spirited serious benefits. Two of these concepts turned out to affect the dynamics of the formulation of the rules of marriage in Indonesia. In Article 2 of the Act No.1 / 1974 of the marriage has been declared that the marriage is valid if conducted according to religion and belief. Furthermore, a very sharp contradiction is visible on the existence of Presidential Directive 1991 on the Compilation of Islamic Law and Counter Legal Draft of Compilation of Islamic Law. In the CLD-KHI in Article 54 states unequivocally that interfaith marriages are allowed to keep records to fulfill the purpose of marriage, the happiness of the couple. Here, the formulation is consistent with the concept of utilitarianism serious benefits. In the context of human rights, human happiness (the couple) would be used as a right that can not be reduced under any circumstances (non-derogable rights), while the interest of following the religion as an interest that could be reduced in certain circumstances (derogable rights / interests). Keywords: pernikahan, agama, hukum keluarga, dan fiqh